CURRENT UPDATE ON CONGENITAL HEART DISEASE SCREENING IN PREGNANCY - Nuswil Bernolian; Cindy Kesty; Benedictus Wicaksono Widodo (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Congenital Heart Disease (CHD) affects 8 births per 1,000 live births; equivalent to 1.35 million children born with CHD each year. Based on global incidence rate, Atrial Septal Defect (ASD), Ventricular Septal Defect (VSD), and Atrioventricular Septal Defect (AVSD) are found on 54.5% of CHD cases. Genetic factors are known to involve in CHD. Moreover, it can also be caused by environmental and infectious factors. Ultrasonography has been widely utilized to screen CHD at 18-22 weeks gestational age. Screening aims to measure heart rate, heart size, heart position, four chamber of the heart, pericardium, atrium, ventricles, atrioventricular junctions, and ventriculoatrial junctions. Doppler echocardiography becomes primary diagnostic tools in CHD patients because of its high sensitivity and specificity, safety, and noninvasiveness. Follow-up examination is indicated on a few conditions. Maternal indications include autoimmune antibody, family history of defects, in vitro fertilization, maternal metabolic disease, or teratogenic exposure. Fetal indications include abnormal screening result, family history of CHD, abnormal heart rhythm, chromosomal abnormalities, extracardiac abnormalities, hydrops, or monochorionic twin pregnancy. With increased rate of CHD, better screening and follow-up should be conducted to achieve acceptable detection rate.